Dystocia due to fetal anasarca in a cross-bred cow - KUMAR, SURESH; BHATT, PRAKASH; PRASAD, J K; RAWAT, A K; MAURYA, S N; KUMAR, SATYENDRA (The Indian Journal of Animal Reproduction, 2023)
The excessive accumulation of fluid subcutaneously or in other parts of fetus resulting into excessive generalized oedema of the fetus is usually termed as fetal anasarca. This usually causes dystocia at parturition because of its abnormal size. The emphysema of such fetus further complicates the condition. It occurs due to autosomal recessive gene. A similar case is placed on record in a crossbred cow.